Sustainable management of transboundary pests requires holistic and inclusive solutions - Boddupalli, P.M.; Carvajal-Yepes, Mónica; Kumar, P. Lava; Kawarazuka, Nozomi; Liu, Yanyan; Mulema, Annet A.; McCutcheon, S.; Ibabao, Xenina (Springer, 2022)
Globalization and changing climates are aggravating the occurrence and impacts of transboundary pests, and driving the emergence of new threats. Most of the low- and middle-income countries in Africa, Asia and Latin America are not fully prepared in terms of surveillance, diagnostics, and deployment of plant health solutions due to several factors: adequate investment is lacking; knowledge is inadequate; and connections from the local to global, and global to local are insufficient. Effectively countering the current and emerging threats to plant health requires a holistic approach that includes: 1) globally coordinated diagnostic and surveillance systems; 2) epidemiological modelling, risk assessment, forecasting and preparedness for proactive management and containment; and 3) implementation of context-sensitive, eco-friendly, gender-responsive and socially inclusive integrated disease and pest management approaches to reduce the impacts of devastating transboundary pests and diseases. Despite several success stories where major pests and diseases have been brought to control through integrated approaches, further multi-institutional and multi-disciplinary efforts are necessary. Plant health management requires stronger interface between the biophysical and social sciences, and empowerment of local communities. These reflections derive from the proceedings of a webinar on “Transboundary Disease and Pest Management,” organized by CGIAR (Consultative Group on International Agricultural Research) on March 3, 2021, in recognition of the United Nations designated International Year of Plant Health.